Effects of Religious Instrumental Music Therapy on Pain Level in Breast Cancer Patients - Fujianti, Mery Eka Yaya; Wahyuni, Ida; Holis, Willi (Genius Journal, 2024)
Introduction: Breast cancer is a type of cancer that frequently occurs in women, characterized by hard, movable lumps with an irregular shape. The main complaint in cancer patients is pain. Pain management can be performed through instrumental music therapy. Instrumental music therapy provides a relaxing effect due to the balanced tempo and harmony of tones. Objective: This study aims to analyze the impact of religious instrumental music therapy on pain levels in breast cancer patients. Method: This research is a quantitative study employing a quasi-experimental design, specifically utilizing a pre-test post-test control group design approach. This study's population is made up of 183 breast cancer patients. The research was conducted in the chemotherapy room of RSUD Dr. H. Moh. Anwar Sumenep from September to November 2022. The sampling technique used is non-probability sampling with a purposive sampling method, based on inclusion criteria. A total of 54 participants were selected and allocated to the intervention group and the control group. The McGill Pain Questionnaire (MPQ) is used to measure pain. Data analysis is performed using the Wilcoxon statistical test with a significance level of p<0.05. Data analysis is carried out using SPSS 24 software. Result: The results of the bivariate test analysis showed that the pain level in the experimental group significantly changed before and after receiving the religious instrumental music therapy intervention, with a p-value < 0.05. In contrast, the control group showed no significant change, with a p-value of 1.000, as no intervention was provided. Conclusion: Religious instrumental music therapy has proven to be effective in reducing pain levels in breast cancer patients at RSUD Dr. H. Moh. Anwar Sumenep.